COVID-19 – neuropathological point of view, pathobiology, and dilemmas after the first year of the pandemic struggle - Sieracka, Jaśmina; Sieracki, Przemysław; Kozera, Grzegorz; Szurowska, Edyta; Gulczyński, Jacek; Sobolewski, Piotr; Kloc, Wojciech; Iżycka-Świeszewska, Ewa (Folia Neuropathologica, 2021)
This article constitutes a summary of the knowledge on the involvement of the nervous system in COVID-19, concerning its general pathobiology, clinical presentation and neuropathological features as well as the future directions of investigation. Variable definitions, selection bias, mainly retrospective analyses of hospitalized patients and different methodologies are implemented in the research of this new disease. Central nervous system (CNS) pathology presents most frequently features of non-specific neuroinflammation with microglial activation and lymphoid infiltrations, ischemic/hypoxic encephalopathy, acute cerebrovascular disease, and microthrombi. Some brain specimens remain unaffected or show only non-specific changes of the critical status. Interpretations of the neuropathological findings are not always balanced in a clinical context and discrepant in consequence. Designing of longitudinal neuropathological studies, more frequent autopsies, and building of COVID-19 brain banks, together with neuroimaging analyses is essential. Genetic predispositions or immunological factors corresponding to the disease profile as well as cerebrospinal fluid (CSF) or serum biomarkers of COVID-19, the impact of different virus variants and influence of the therapy need to be identified. The mechanisms causing neuroCOVID and cognitive impairment – whether they are infectious, toxic, vascular or metabolic – create other aspects under research. There are also many existential questions about post-COVID and delayed sequelae of the infection. The fight with pandemic is a challenge for the global society, with neuropathologists and neuroscientists as important allies in struggle for understanding and conquering COVID-19.